Fabric Response to COVID-19 Ozone Sterilization (Journal of Fiber Bioengineering and Informatics, 2020)
Limited availablilty of personal protective equipment (PPE) during the current COVID-19 pandemichas led to frequent unsafe reuse of personal protective clothing by healthcare workers and the public.The application of ozone gas to sterilize PPEs for reuse has been proposed. However, the potentialdamage inflicted on the fabrics has not been reported in the scientific literature. A study was conductedto investigate the changes in fabric elasticity that may be associated with a two-hour exposure to ozonegas at a concentration of 17 ppm. No significant material degradation was found. The results suggestthat use of ozone gas to sterilize PPEs for reuse against COVID-19 virus can be effective.
Keywords: Fabric elasticity; Ozone sterilization; PPE Reuse